2020
DOI: 10.1051/0004-6361/202037628
|View full text |Cite
|
Sign up to set email alerts
|

Detection of deuterated molecules, but not of lithium hydride, in the z = 0.89 absorber toward PKS 1830−211

Abstract: Deuterium and lithium are light elements of high cosmological and astrophysical importance. In this work we report the first detection of deuterated molecules and a search for lithium hydride, 7LiH, at redshift z = 0.89 in the spiral galaxy intercepting the line of sight to the quasar PKS 1830−211. We used ALMA to observe several submillimeter lines of ND, NH2D, and HDO, and their related isotopomers NH2, NH3, and H218O, in absorption against the southwest image of the quasar, allowing us to derive XD/XH abund… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 54 publications
3
16
0
Order By: Relevance
“…The astrochemical models of deuterated species predict that HDO is abundant regardless of the extragalactic environment (starburst, cosmic-rays-enhanced environments, low-metallicity, and high-redshift galaxies) and should be detectable with ALMA in many diverse galaxies (Bayet et al 2010). Our results for the LMC and the detection of HDO toward the z=0.89 absorber against the quasar PKS 1830−211 by Muller et al (2020) are in agreement with these model predictions. Furthermore, our work demonstrates the utility of HDO as a tracer of H 2 O chemistry, which is more readily accessible than H 2 O using ground-based, mm-wave observations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The astrochemical models of deuterated species predict that HDO is abundant regardless of the extragalactic environment (starburst, cosmic-rays-enhanced environments, low-metallicity, and high-redshift galaxies) and should be detectable with ALMA in many diverse galaxies (Bayet et al 2010). Our results for the LMC and the detection of HDO toward the z=0.89 absorber against the quasar PKS 1830−211 by Muller et al (2020) are in agreement with these model predictions. Furthermore, our work demonstrates the utility of HDO as a tracer of H 2 O chemistry, which is more readily accessible than H 2 O using ground-based, mm-wave observations.…”
Section: Discussionsupporting
confidence: 87%
“…The first, and until now the only, extragalactic detection of HDO was reported by Muller et al (2020). Using the Atacama Large Millimeter/submillimeter Array (ALMA), Muller et al (2020) detected the HDO J Ka,Kc = 1 01 -0 00 absorption line at 464.9245 GHz in a spiral galaxy at a redshift (z) of 0.89 on the line of sight toward the quasar PKS 1830−211. Here, we report the first detection of HDO toward extragalactic hot molecular cores.…”
Section: Introductionmentioning
confidence: 99%
“…Martín et al (2006) reported a tentative detection of DNC and N 2 D + in the nucleus of the starburst galaxy NGC 253. Most recently, Muller et al (2020) reported the detection of ND, NH 2 D, and HDO with ALMA at redshift z = 0.89 in the spiral galaxy intercepting the line of sight to quasar PKS 1830−211. We detected deuterated formaldehyde (HDCO), deuterated hydrogen sulfide (HDS), and deuterated water (HDO) toward hot cores 2 A (HDCO and HDO) and 2 B (HDO), and a hot core candidate 2 C (HDS).…”
Section: Line Identificationmentioning
confidence: 99%
“…A total of 54 molecular species (not counting isotopologues) have been identified in the parts of the spectrum surveyed to date: a 20 GHz-wide band at 7-mm wavelength with the ATCA interferometer and the Yebes 40-m telescope, a 8 GHz-wide band at 3-mm with NOEMA, and a 38 GHz-wide band between 3-mm and 0.6-mm with ALMA (Muller et al, 2011;Muller et al, 2014;Muller et al, 2016;Muller et al, 2017) and references therein (Muller et al, 2020;Tercero et al, 2020).…”
Section: Molecules Inside An Arm Of a Spiral Galaxy At Redshift Z = 089mentioning
confidence: 99%